The Nickel Syndicate, 1901-1939 - Boyce, Gordon (School of Management Working Papers, 1995)
In 1901, several British armament firms formed the Steel Manufacturers' Nickel Syndicate Ltd. to exert combined purchasing power against La Societe de Nickel, then the world's only major supplier of nickel. Although membership in the Syndicate changed over time, new sources of demand for nickel arose, and additional suppliers emerged, the Syndicate operated successfully until World War II. Conventional economics and organisational theory predict that this type of co-operative arrangement is necessarily doomed to dissolution. To explain why the Syndicate endured for nearly forty years in the face of significant shifts in demand and supply we need to examine relations within the Syndicate and between the Syndicate and its suppliers in contractual terms. In the case of the former relationship, underlying communication channels gave the Syndicate a strong bargaining position, but by making judicious use of this power, the organisation was able to elicit ongoing co-operation from its suppliers. Within the Syndicate, members derived significant financial advantages from association. We can measure these benefits and show how the Syndicate conducted its activities to ensure that these gains were not absorbed by operating expenses.